The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bmj.k1036
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiovascular risk in rheumatoid arthritis: mechanisms and implications

Abstract: Rheumatoid arthritis is a systemic autoimmune disease characterized by excess morbidity and mortality from cardiovascular disease. Mechanisms linking rheumatoid arthritis and cardiovascular disease include shared inflammatory mediators, post-translational modifications of peptides/proteins and subsequent immune responses, alterations in the composition and function of lipoproteins, increased oxidative stress, and endothelial dysfunction. Despite a growing understanding of these mechanisms and their complex int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
266
3
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(333 citation statements)
references
References 177 publications
7
266
3
18
Order By: Relevance
“…CVD remains a major cause of death and is significantly increased in people with RA compared to the general population , a fact recognized by the addition of RA as an independent risk factor in CVD risk algorithms such as QRISK2 and QRISK3 . The relative contribution of classic CVD risk factors and novel mechanisms related to systemic inflammation to the excess CVD mortality of RA is still debated , and there have been no clinical end point trials assessing the effect of statins, or any other primary prevention strategy, in this population. Some small studies have shown that statins reduce surrogate measures of atherosclerotic events, for example, arterial stiffness or carotid plaque , while a few cohort studies have suggested that statin use is associated with survival gains and statin discontinuation with poorer survival in RA.…”
Section: Discussionmentioning
confidence: 99%
“…CVD remains a major cause of death and is significantly increased in people with RA compared to the general population , a fact recognized by the addition of RA as an independent risk factor in CVD risk algorithms such as QRISK2 and QRISK3 . The relative contribution of classic CVD risk factors and novel mechanisms related to systemic inflammation to the excess CVD mortality of RA is still debated , and there have been no clinical end point trials assessing the effect of statins, or any other primary prevention strategy, in this population. Some small studies have shown that statins reduce surrogate measures of atherosclerotic events, for example, arterial stiffness or carotid plaque , while a few cohort studies have suggested that statin use is associated with survival gains and statin discontinuation with poorer survival in RA.…”
Section: Discussionmentioning
confidence: 99%
“…The heightened risk of CVD and CVD-related mortality in RA has been well established [5, 17, 18]. As a result, numerous efforts have been undertaken to enhance the identification of CVD and its risk factors as well as treating both RA and modifiable risk factors as a means of preventing premature CVD mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the general population, patients with RA have a 8-15 year reduced life expectancy [1] due principally to cardiovascular complications, most commonly atherosclerotic diseases and congestive heart failure (CHF) [2]. Although the pathophysiologic mechanism is not clearly defined, the chronic inflammatory state of RA itself seems to play a pivotal role in both vascular changes and impaired myocardial function [3,4]. Previous studies have shown that asymptomatic left ventricular myocardial dysfunction is common, both systolic and diastolic abnormalities at rates of; 45 and 31% respectively [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%